Quality of life of patients with multiple sclerosis treated at a health institution in Medellín (Colombia) - Orozco-González, Catalina; Vagner-Ramírez, Basilio; Salas-Zapata, Carolina (Universidad y Salud, 2019)
Introduction: Health-related quality of life (HRQL) in multiple sclerosis (MS) patients can be affected by physical, clinical and sociodemographic factors. Objective: To determine the effect of sociodemographic, clinical and physical factors on the quality of life (QL) of patients with MS. Materials and methods: The WHO WHOQOL-BREF instrument was applied to 173 patients of a health institution. Descriptive analysis of sociodemographic, clinical and physical characteristics and their QL scores were performed. The association between global QL with sociodemographic, clinical and physical factors was observed; finally, through multivariate analysis. Results: 80.3% were women, the median age was 43 years (IQR = 51-35). Fatigue was the most frequent symptom (71%). The risk factors for worse QL were: female sex (RP = 6.92. 95% CI 1.8-26.58), abnormal sphincter control (RP = 6.10 95% CI 1.26-29.51), cognitive disorders (RP = 4.46 95% CI 1.07-18.56), risk of depression (RP = 3.82 95% CI 1 , 01-14,38) and lack of physiotherapy (RP = 4.48 95% CI 1.08-18.34). Conclusions: The effect of QL in MS is variable and depends on sociodemographic and clinical factors. Evaluating the (HRQL) in clinical practice facilitates the understanding of the behavior and needs of the patient required for risk factors intervention.